THE EFFECTIVENESS OF SALES PROMOTION AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF FLASH COFFEE INDONESIA - Husnan Nurjuman; Andhalia Liza Marie; Ronny Yudhi Septa Priana (Sean Institute, 2023)
In Jakarta itself, coffee shops are growing and getting more and more, so that every coffee shop is competing with each other to get regular customers by making various kinds of interesting promos. Usually every coffee shop has a way to make the promo sound interesting. Therefore, researchers conducted this study with the aim to determine the effect of Sales Promotion (X1) and Quality of Service (X2) of the Customer Satisfaction Flash Coffee Indonesia (Y). This study used a sample of 97 respondents who were measured using a questionnaire consisting of 25 statements. The tests carried out in this study were validity tests, reliability tests, descriptive statistical analysis, coefficient of determination, simple linear analysis, multiple linear analysis, correlation tests and hypothesis testing. Based on the research that has been done, namely Sales Promotion conducted by Flash Coffee Indonesia with a mean of 3.36 in the very good category, Service Quality at Flash Coffee with a mean of 3.55 in the very good category, and Customer Satisfaction Flash Coffee with a mean of 3.35 in the very satisfied category. Sales Promotion has a fairly strong relationship with Customer Satisfaction. Service Quality has a strong relationship with Customer Satisfaction. Sales Promotion (X1) has an influence on Customer Satisfaction Flash Coffee (Y) by 34.6% and the remaining 65.4% is influenced by other factors not examined in this study. Quality of Service (X2) to give effect to the Customer Satisfaction Flash Coffee (Y) amounted to 45.1% and the remaining 54.9% influenced by other factors not examined in this study. Sales Promotion and Service Quality together affect Customer Satisfaction Flash Coffee by 48.4% and the remaining 51.6% is influenced by other factors not examined in this study.